2013
DOI: 10.1021/ef401713f
|View full text |Cite
|
Sign up to set email alerts
|

Release of Inorganic Trace Elements from Dried Distillers Grains with Solubles during Gasification at 600–1400 °C

Abstract: This work focused on the release of alkali metals (K and Na) and non-metals (S, Cl, and P) during high-temperature gasification of dried distillers grains with solubles. The release experiments were performed at 600–1400 °C in a flow channel reactor. Hot-gas analysis was performed by a molecular beam mass spectrometer. The underlying release mechanisms are discussed with dependence upon the temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Potassium in biomass mainly exists in four forms including water-soluble (usually more than 50%), ion-exchangeable organic K, acid-soluble K, and insoluble K . During thermal conversions, some of the K contents can be released through sublimation of inorganic K and decomposition of organic K. Most of the K is released in the gaseous form of KCl, KOH, or atomic K depending on the specific conditions. , It was found previously that the presence of K in fuel ash can increase the total gas yield and reduce tar formation during gasification. However, the presence of K in gasifiers could increase the propensity of K reacting with the product gas that causes alkali-induced corrosion and fouling of heat-transfer surfaces in downstream components .…”
Section: Introductionmentioning
confidence: 99%
“…Potassium in biomass mainly exists in four forms including water-soluble (usually more than 50%), ion-exchangeable organic K, acid-soluble K, and insoluble K . During thermal conversions, some of the K contents can be released through sublimation of inorganic K and decomposition of organic K. Most of the K is released in the gaseous form of KCl, KOH, or atomic K depending on the specific conditions. , It was found previously that the presence of K in fuel ash can increase the total gas yield and reduce tar formation during gasification. However, the presence of K in gasifiers could increase the propensity of K reacting with the product gas that causes alkali-induced corrosion and fouling of heat-transfer surfaces in downstream components .…”
Section: Introductionmentioning
confidence: 99%
“…9,13 The vapor K species in the product gas were comprehensively investigated by online molecular beam mass spectrometry, and it was found that the volatilization of K was mainly in the form of KCl, KOH, or atomic K depending upon specific conditions. 15,18 In addition to heat treatment conditions, the K release was also affected by the relative Cl concentration and other inorganic constituents. It was revealed that Cl facilitated K release through sublimation of KCl, while Si and Al suppressed it by forming stable K−Si−Al compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was revealed that partitioning of K in gaseous phase and residual char was closely related to the temperature, atmosphere, heating rate, , and other inorganic elements in biomass. The release of K would be promoted at an elevated temperature and under combustion conditions, and the inlet of steam might facilitate K volatilization via widening or creating pores during char steam gasification . The influence of heating rates on the release of alkali metals was dependent upon their occurrence forms and experimental conditions, and there was no agreement on the relationship between them. , The vapor K species in the product gas were comprehensively investigated by online molecular beam mass spectrometry, and it was found that the volatilization of K was mainly in the form of KCl, KOH, or atomic K depending upon specific conditions. , In addition to heat treatment conditions, the K release was also affected by the relative Cl concentration and other inorganic constituents. It was revealed that Cl facilitated K release through sublimation of KCl, while Si and Al suppressed it by forming stable K–Si–Al compounds. ,, On the basis of the above-mentioned findings, mechanisms for K release were gradually developed and the K release was usually ascribed to sublimation of inorganic K and decomposition of organic K. …”
Section: Introductionmentioning
confidence: 99%
“…The intensity time profiles (qualitative data) of the species [ 34 H 2 S + ( m / z 34), 36 HCl + ( m / z 36), 39 K + / 39 NaO + ( m / z 39), 51 V + ( m / z 51), 56 KOH + ( m / z 56), 58 NaCl + ( m / z 58), 60 COS + / 60 NaCl + ( m / z 60), 64 SO 2 + ( m / z 64), and 74 KCl + ( m / z 74)] under investigation are given in Figure . The given results represent conditions in an entrained flow gasifier as recently shown. …”
Section: Resultsmentioning
confidence: 64%
“…As reported recently, the experimental conditions during the devolatilization phase are closer to gasification conditions and the experimental conditions of the char reaction phase are closer to combustion conditions. To represent gasification conditions, the semi-quantitative analysis was carried out for the devolatilization phase only. The influence of the fuel composition on the release of alkali, sulfur, and chlorine species was determined by comparison of the semi-quantitative results to the results of the chemical analysis (Table ).…”
Section: Resultsmentioning
confidence: 80%